2016
DOI: 10.1098/rspb.2016.0235
|View full text |Cite
|
Sign up to set email alerts
|

Laetoli footprints reveal bipedal gait biomechanics different from those of modern humans and chimpanzees

Abstract: Bipedalism is a key adaptation that shaped human evolution, yet the timing and nature of its evolution remain unclear. Here we use new experimentally based approaches to investigate the locomotor mechanics preserved by the famous Pliocene hominin footprints from Laetoli, Tanzania. We conducted footprint formation experiments with habitually barefoot humans and with chimpanzees to quantitatively compare their footprints to those preserved at Laetoli. Our results show that the Laetoli footprints are morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 39 publications
3
73
1
Order By: Relevance
“…These changes started to appear in Australopithecus afarensis at approximately 3.6 million years ago (Mya); it has been extensively studied via the Laetoli footprints ( Figure 1) discovered by Mary Leaky in 1978 near Olduvai Gorge in Tanzania [21][22][23]. On the other that hominids adaptations, particularly pelvic re-designing, were far different for example that of Oreopithecus bambolii [24].…”
Section: Discussionmentioning
confidence: 99%
“…These changes started to appear in Australopithecus afarensis at approximately 3.6 million years ago (Mya); it has been extensively studied via the Laetoli footprints ( Figure 1) discovered by Mary Leaky in 1978 near Olduvai Gorge in Tanzania [21][22][23]. On the other that hominids adaptations, particularly pelvic re-designing, were far different for example that of Oreopithecus bambolii [24].…”
Section: Discussionmentioning
confidence: 99%
“…afarensis. These footprints were made by bipedal hominins moving with an extended hip and extended knee, though perhaps with a gait different from that practiced by modern humans . The prints bear a strong resemblance to those made by modern humans today; however, there are several key differences.…”
Section: Australopithecus Feetmentioning
confidence: 99%
“…These footprints were made by bipedal hominins moving with an extended hip and extended knee, 86 though perhaps with a gait different from that practiced by modern humans. 87 The prints bear a strong resemblance to those made by modern humans today 13,88 ; however, there are several key differences. One hominin (G1) experienced less medial weight transfer than is typically seen in humans 52,87 and analyses suggest that while the medial arch was present, it was likely reduced relative to most humans today.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Others have contested this conclusion (e.g., Meldrum et al, 2011). In fact, a recent analysis strongly suggested that the Laetoli footprints were significantly different from those of a modern human walking barefoot, and actually in some ways more similar to chimpanzee footprints (Hatala et al, 2016). …”
mentioning
confidence: 99%